2004
DOI: 10.1007/s00253-003-1438-9
|View full text |Cite
|
Sign up to set email alerts
|

Toward rational control of Escherichia coli O157:H7 by a phage cocktail

Abstract: Twenty six phages infected with Escherichia coli O157:H7 were screened from various sources. Among them, nine caused visible lysis of E. coli O157:H7 cells in LB liquid medium. However, prolonged incubation of E. coli cells and phage allowed the emergence of phage-resistant cells. The susceptibility of the phage-resistant cells to the nine phages was diverse. A rational procedure for selecting an effective cocktail of phage for controlling bacteria was investigated based on the mechanism of phage-resistant cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(162 citation statements)
references
References 7 publications
12
143
0
Order By: Relevance
“…26,[33][34][35] A number of authors have demonstrated the efficacy of either single or cocktail phage treatments in the laboratory but only a few have shown any meaningful reduction in vivo. [23][24][25]27,28,36,37 Early studies examining phage populations in livestock were born of a concern that they might negatively affect the microbial ecology of the gut (especially the rumen) and thus reduce animal productivity; however, it was found that phage actually help maintain microbial diversity and balance. 38,39 These initial studies centered on bovine ruminal phages, but more recent O157:H7 phage research has moved to the recto-anal junction, the demonstrated major site of colonization in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…26,[33][34][35] A number of authors have demonstrated the efficacy of either single or cocktail phage treatments in the laboratory but only a few have shown any meaningful reduction in vivo. [23][24][25]27,28,36,37 Early studies examining phage populations in livestock were born of a concern that they might negatively affect the microbial ecology of the gut (especially the rumen) and thus reduce animal productivity; however, it was found that phage actually help maintain microbial diversity and balance. 38,39 These initial studies centered on bovine ruminal phages, but more recent O157:H7 phage research has moved to the recto-anal junction, the demonstrated major site of colonization in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, bacteriophages have a very narrow spectrum for bacterial inhibition and high host specificity for infection (30). Therefore, to increase the phage infection range and inhibition efficiency, phage cocktails containing different phages have been developed and used for inhibition of pathogens such as Salmonella and E. coli O157:H7 (52,67,69). Although a few broad-host-range phages have been reported (6,31,34), the bacteriophage AR1 is the only phage reported to date that can inhibit both Salmonella and E. coli O157:H7 (24,42).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report identifying specific infection and inhibition of major foodborne pathogens, Salmonella Typhimurium and E. coli O157:H7, by a single bacteriophage. Various components of the bacterial outermost cell layer, such as flagella (61,63), O antigen of LPS (4,39,47), OmpC (28,67,72), and BtuB (29,35), are used as bacteriophage receptors. Identification of the phage receptor is essential for the application of phages in the biocontrol of pathogens (25).…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, in vitro experiments demonstrated that using ZRP1 above a certain MOI threshold immediately inhibited the growth of host bacteria, and the results indicate that ZRP1 performed better against ZR1 at a higher MOI than a lower one. However, the regrowth observed after several hours indicated the substitution of phage-resistant bacteria (Tanji, et al, 2004). Intravenous injection of pathogenic E. coli ZR1 caused haemorrhages of the large intestine and led to a systemic infection involving the liver.…”
Section: Discussionmentioning
confidence: 99%